Analysis of early morphological and functional perivulnar changes in the mucosa of the cecum after suturing with different surgical threads - S.M. Bilash; O.M. Pronina; I.V. Ksyonz; M.M. Koptev; Ya.O. Oliinichenko; B.S. Kononov (Хірургія дитячого віку)
The correct choice of suture material is the key to successful treatment in abdominal surgery, particularly pediatric surgery. Given this, experimental studies on the effect of sutures made with different surgical threads are one of the most urgent surgery needs.